Perbedaan nilai gizi susu sapi setelah pasteurisasi non termal dengan HPEF (High Pulsed Electric Field) - Budi Hariono; Feby Erawantini; Azamataufiq Budiprasojo; Trismayanti Dwi Puspitasari (AcTion: Aceh Nutrition Journal, 2021)
Cow's milk is the secretion of a cow that has perfect nutritional value but is easily damaged. Efforts to extend the shelf life of milk, milk is usually stored in a box freezer or by thermal pasteurization. However, this thermal processing can change the smell, taste, colour and reduce the nutritional content of milk, especially protein, which is a heat resistant substance. Alternative non-thermal technology that HPEF can apply. The method of this research was descriptive, describing the nutritional value of milk before and after had been HPEF Implementation. After non-thermal pasteurized cow's milk with HPEF, the nutritional value of cow's milk was better than fresh cow's milk. In unprocessed milk with HPEF, the fat content decreased by 3,77%. Protein content increased 0,15%, lactose 0,29%, and increased mineral content 0,05%. The TPC test on milk showed 6,91 x 102 cfu/ml. HPEF implementation can effectively reduce fat levels, increase protein, lactose levels, and increase mineral levels in milk. Non-thermal pasteurized cow's milk with HPEF can be immediately ready for consumption